Pancasila Implementation Strategy as Dar al-ahdi wa al-syahadah - Ma'mun Murod; Tria Patrianti; Lusi Andriyani; Usni Usni; Djoni Gunanto (Universitas Muhammadiyah Jakarta, 2022)
Pancasila has become an agreement as to the final form of state philosophy or ideology. Pancasila is considered a